2020
DOI: 10.1109/access.2020.3021746
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Human Body and Brain Monitoring During Horseback Riding Simulator by Means of Inertial Motion Capture and EEG Systems

Abstract: One type of effective muscular disorders therapy is horseback riding. The main objective of the present study is developing a physiotherapeutic simulator (concept proof) instead of a real horse though employing the Electroencephalography (EEG) amplifier and inertial motion capture system (IMCS). In the experiment, the professional and non-professional rider's body movements and brain-behaviors monitored during the horseback riding simulator. The computational analysis for identifying the alterations of the pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In total, two tasks were conducted during the real-time experiment, i.e., imagining making a fist once during the 2500 ms period, and similarly imagining opening their hand during this same period. During the experiment, a portable Enobio-32 amplifier with 32 dry electrodes (Shown in Figure 2) was used for EEG data collection, in which the sampling frequency rate was set to 500 Hz [40]- [42]. MATLAB-2017a software was used for signal processing in offline and real-time modes.…”
Section: Methodsmentioning
confidence: 99%
“…In total, two tasks were conducted during the real-time experiment, i.e., imagining making a fist once during the 2500 ms period, and similarly imagining opening their hand during this same period. During the experiment, a portable Enobio-32 amplifier with 32 dry electrodes (Shown in Figure 2) was used for EEG data collection, in which the sampling frequency rate was set to 500 Hz [40]- [42]. MATLAB-2017a software was used for signal processing in offline and real-time modes.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroelectrics NIC OFFLINE software was used for EEG data processing. As a result, the asymmetry shift in rider's external hip and back regions was identified, and it was found that the frontal lobes, the temporal and the parietal areas of the brain were significantly activated (Byzova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In medical applications, they are one of the most important technologies. For example, electroencephalograms (EEG) have recently been used for brain recording, as it is less expensive and more safe in magnetic fields [ 11 , 12 ]. For illustrating the importance of these medical devices, consider the example of a particle accelerator typically used for cancer diagnosis and prediction of initial treatment.…”
Section: Introductionmentioning
confidence: 99%